Value investment with machine learning - Wang, Jiwei (Nanyang Technological University, 2024)
This thesis investigates the application of machine learning techniques to value investment strategies within the Chinese A-share market, utilizing the BigQuant platform and the advanced StockRanker model. Our research focuses on integrating fundamental and technical factors to enhance predictive accuracy and investment performance. Initial models, based solely on fundamental factors, achieved an annualized return of 10% but exhibited significant volatility. By incorporating technical indicators, we developed a combined model that improved the annualized return to 27.8%.